Analisa injeksi Surfaktan+KCL untuk meningkatkan perolehan produksi minyak pada formasi AB-2b di formasi air benakat - Firdaus Firdaus; Rohima Sera Afifah (Sekolah Tinggi Teknologi MIGAS, 2022)
This research is a study of surfactant injection to increase oil production in layer AB-2B Meruap field managed by BWP MERUAP. Meruap field has decreased oil production. To increase production, one way to do this is by doing Enhanced Oil Recovery (EOR) so that oil production in the AB-2B layer increases. EOR is an advanced drainage from the reservoir. Surfactants and KCl as injection fluid in this layer are selected based on the results of laboratory data that have been carried out on the AB2B layer Meruap field. surfactant injection is used to reduce the fluid oil interface tension, where oil is trapped by capillary pressure and cannot move, so that the trapped oil can be removed by injecting the surfactant. Mixing surfactant with oil to form an emulsion that will reduce capillary pressure. The results obtained in the AB-2B Meruap field after surfactant injection was carried out was increased oil production